Mathematical Literacy Reviewed from the Student's Cognitive Style in the Problem Based Learning Learning Model Assisted by the Learning Management System - Rahayu, Diana Urip; Mulyono, Mulyono; Nur Cahyono, Adi (Universitas Negeri Semarang, 2021)
This study aims to find out the PBL model assisted by LMS is effective in improving mathematical literacy skills, to determine the effect of mathematical literacy skills on the PBL learning model assisted by LMS in terms of students' cognitive styles, and to determine the description of mathematical literacy in terms of students' cognitive styles in the PBL-assisted learning model. LMS. This type of research is explanatory sequential mixed methods. Non-equivalent research design (Pretest-Posttest) Control Group Design. Data collection techniques using tests, questionnaires, observation, documentation, and interviews. The research was conducted in class XI SMA N 1 Semarang. The research sample is in class XI MIPA 4 and XI MIPA 5. Based on the results of the study it was found that (1) PBL Learning Model Assisted LMS Effectively Improves Mathematical Literacy. (2) The positive effect between students' cognitive style (visualizer-verbalizer) and mathematical literacy in the PBL learning model assisted LMS is 51.3%. (3) Visualizer subjects who have high literacy skills meet 6 aspects of 7 aspects of mathematical literacy indicators, visualizer subjects who have moderate mathematical literacy skills meet only 5 aspects and visualizer subjects who have low mathematical literacy skills meet 3 aspects. (4) Verbalizer subjects with high criteria in their mathematical literacy ability meet 5 aspects of 7 aspects of mathematical literacy indicators, verbalizer subjects who have moderate mathematical literacy skills meet 4, and verbalizer subjects who have low mathematical literacy skills meet only 3 aspects.